Statesman's yearbook : the politics, cultures and economies of the world 2018 - Martin, Frederick, 1864-1883.; Keltie, John Scott, Sir, 1883-1926.; Epstein, Mortimer, 1927-1946.; Steinberg, S. H., 1946-1964.; Paxton, John, 1969-1990.; Hunter, Brian, 1990-1997.; Turner, Barry, 1997-2014. (London : Palgrave MacMillan, 2018)
This classic reference work presents a political, economic and social account of every country of the world together with facts and analysis.
Keywords: Gazetteers; Economic history -- 21st century; World politics -- 21st century; Yearbooks; Quick Ref. Collection; Reference sources; Reference works; Periodicals; Reference works; Gazetteers